P216 Cardiac amyloidosis is not a single disease: an echocardiographic study of light chain vs transthyretin forms. (17th January 2020) - Adam, R D; Jercan, A; Badelita, S; Coriu, D; Stan, C; Serban, M; Beladan, C; Rosca, M; Balahura, A M; Ginghina, C; Popescu, B A; Jurcut, R
Abstract: Background: Cardiac amyloidosis (CA) is described as one entity. However, several subtypes of amyloid can infiltrate the heart: light chain (AL) and tranthyretin (ATTR) are the most common. Purpose: To characterize the specific findings of the CA subtypes as a tool to aid differential diagnosis between AL and ATTR CA. Material and methods: Consecutive patients with CA were evaluated by clinical examination, ECG, cardiac biomarkers and echocardiography with both conventional and myocardial deformation study of the left ventricle (LV), left atrium (LA) and right ventricle (RV). Amyloid subtype was described using light chain assessment for AL-CA and 99Tc-HMPD scintigraphy and TTR gene sequencing for ATTR-CA. Results: 32 patients with CA were included, 13 with ATTR and 19 with AL. Patients in AL group were significantly older, with higher levels of cardiac biomarkers. At similar LV EF and wall thickness, they had lower GLS. LA function parameters were also lower in AL pts (table). Using ROC curves, the best predictors for AL diagnosis were NTproBNP (AUC 0.937) and Tn levels (AUC 0.958), as well as LV GLS and pericardial fluid presence (both AUC 0.750). Conclusions: At similar LV wall thickness and ejection fraction, cardiac dysfunction appears to be more severe in AL pts, with lower global LV longitudinal strain, worse LA function, higher sPAP and NTproBNP.